HYPNOTIC-SEDATIVE ACTIVITY TEST OF 70% ETHANOL EXTRACT OF LETTUCE (Lactuca sativa L.) IN MALE WHITE MICE SWISS WEBSTER STRAIN - Sadino, Asman; Renggana, Hesti; Suwendar, Suwendar; Apriani, Riza; Nurhandayani, Yuni (Jurnal Ilmiah Farmako Bahari, 2024)
Humans who use medicines for insomnia may experience a variety of adverse effects, including dependence. Traditional medicine frequently uses lettuce (Lactuca sativa L.) to treat various conditions, including sleep difficulties. Terpenoids, which are secondary metabolites found in lettuce plants, are to blame for this. This study aimed to see if an ethanolic extract of lettuce leaf had any sedative-hypnotic activity in Swiss Webster strain male white mice induced by phenobarbital at a dose of 90 mg/KgBB intraperitoneally. In this study, the post-test-only control strategy was employed. The animals were divided into six groups (n = 4): negative (aqua dest), positive (Na-CMC 0.5%), comparison (diazepam 1.3 mg/KgBB), and ethanolic extract of lettuce leaf at doses of 300 mg/KgBB, 400 mg/KgBB, and 500 mg/KgBB. The parameters observed in this study were a combination of parameters from previous studies, namely the number of falls, sleep onset, and sleep duration in mice. The data obtained were then processed statistically using the one-way ANOVA (analysis of variance) and post-hoc test follow-up analysis with the LSD (least significant difference) test. The results showed that the ethanolic extract of lettuce leaves at 300, 400, and 500 mg/KgBB had a sedative-hypnotic effect. Doses of 300 mg/KgBB only increased sleep duration. In contrast, 400 and 500 mg/KgBB increased the number of falls, rapid sleep onset, and increased sleep duration, significantly different from positive controls (p<0.05). The effective dose of ethanolic extract of lettuce leaf as a sedative-hypnotic was 400 mg/KgBB.